2011
DOI: 10.1007/s00280-011-1649-1
|View full text |Cite
|
Sign up to set email alerts
|

Methylseleninic acid inhibits HDAC activity in diffuse large B-cell lymphoma cell lines

Abstract: Purpose: Selenium is a trace element that is fundamental to human health. Research has mainly focussed on its role in cancer prevention, but recent evidence supports its role in established cancer, with high concentrations inducing tumour cell death and non-toxic concentrations sensitising cells to chemotherapy. However, the precise mechanism of selenium action is not clear. The effect of methylseleninic acid (MSA), an organic selenium compound, on HDAC activity in diffuse large B-cell lymphoma cell lines is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…Additionally, a continuous generation of CH 3 SeH might be of importance for successful modulation of NKG2D ligands in vivo to counteract the naturally occurring metabolism of CH 3 SeH into dimethylselenide, trimethylselenonium, or H 2 Se. Notably, the tested Jurkat T cell line, but also other lymphoma cell lines, can generate the volatile selenium metabolites CH 3 SeH, DMDSe, and dimethylselenide in vitro because of the presence of the required and functional enzymes (26,68,80). When taken up by cells, MSA can also be reduced to CH 3 SeH via a nonenzymatic process (81).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a continuous generation of CH 3 SeH might be of importance for successful modulation of NKG2D ligands in vivo to counteract the naturally occurring metabolism of CH 3 SeH into dimethylselenide, trimethylselenonium, or H 2 Se. Notably, the tested Jurkat T cell line, but also other lymphoma cell lines, can generate the volatile selenium metabolites CH 3 SeH, DMDSe, and dimethylselenide in vitro because of the presence of the required and functional enzymes (26,68,80). When taken up by cells, MSA can also be reduced to CH 3 SeH via a nonenzymatic process (81).…”
Section: Discussionmentioning
confidence: 99%
“…For example, both selenite and Se-Met may be metabolized into methylated Se compounds, some of which have cancer chemopreventive effects (113). One example is the inhibition histone deacetylase (HDAC) activity in diffuse large B-cell lymphoma cell lines by methylseleninic acid and the toxic effects this may exert in chemoprevention (125). In addition, some studies have used the selenoorganic compound, ebselen, to show that macrophage and dendritic cell functions are affected by this smallmolecular-weight selenocompound (156,229).…”
Section: Bioactive Forms Of Se and Their Effectsmentioning
confidence: 99%
“…FoxP3, forkhead box P3; RANKL, receptor activator for nuclear factor-jB ligand. been shown to be inhibiited by the small organic selenocompound, methylseleninic acid (125). Chronic inflammation may be an underlying risk factor in the early stages of cancer development, as well as being a key feature of inflammatory bowel disease (IBD).…”
Section: Fig 11 Analyses Of Cell Markers During Activation Of Naivementioning
confidence: 99%
“…One explanation might be that MSA has been suggested to inhibit HDACs. 20 In line with this hypothesis, HDAC inhibitors have been described to upregulate both MHC class I and class II molecules at the cell surface. 60 In addition, MSA has been shown to induce the expression of MICA and MICB in Jurkat cells to the same extent as HDAC inhibitors.…”
Section: Discussionmentioning
confidence: 80%
“…HDACs are involved in the regulation of the gene expression pattern and often overexpressed in tumor cells. In B cell lymphoma and esophageal cancer, MSA reduces HDAC activity 19,20 by modulation of conserved cysteine residues in the catalytic center of HDACs. 21 Different models of tumor-initiation showed that natural killer (NK) cells and the interferon (IFN) system are involved in the immunity of tumors.…”
Section: Introductionmentioning
confidence: 99%